Hierarchically mesoporous/macroporous structured TiO2 for dye-sensitized solar cells1. Issue 91 (9th October 2015) - Qi, Dianyu; Wang, Lingzhi; Zhang, Jinlong
<x xml:space="preserve">Abstract</x> In this study, hierarchical TiO2 with macro- and mesostructure is prepared and applied in dye-sensitized solar cell (DSSCs).